Intelligent 3D Printing Algorithms: Accelerating Additive ‎Manufacturing with Precision and Defect-Free Fabrication - Kathiravan, M.; Kunal, Kishore; Madeshwaren, Vairavel; Lavanya , Pillalamarri; Ganesan, Veeramani; Gupta, Sheifali (International Journal of Basic and Applied Sciences, 2025)
Additive Manufacturing (AM) has transformed modern production by enabling the fabrication of complex geometries with enhanced material ‎efficiency. However, traditional 3D printing techniques often face challenges such as incomplete fusion, material inconsistencies, and thermal ‎warping, which affect overall quality and productivity. This study introduces an intelligent 3D printing framework that integrates Artificial ‎Intelligence (AI) to enable real-time monitoring, defect detection, and adaptive process control, thereby addressing these limitations. The ‎proposed system utilizes Convolutional Neural Networks (CNNs) for computer vision-based quality inspection, enabling the detection of ‎structural anomalies during the printing process. Reinforcement Learning (RL) is employed for dynamic adjustment of parameters like nozzle ‎temperature, deposition speed, and material feed rate in response to real-time feedback, significantly reducing defect occurrence. Adaptive ‎machine learning algorithms like Random Forests and Gradient Boosting also facilitate process optimization and predictive maintenance. ‎Stereolithography (SLA), Selective Laser Sintering (SLS) and Fused Deposition Modeling (FDM) are among the AM platforms that use this AI-‎AI-enhanced closed-loop control approach. Material use, energy efficiency, production time, print quality and defect mitigation have all significantly ‎improved, as confirmed by experimental validation. With its ability to guarantee accuracy and dependability in contemporary 3D printing ‎processes, the framework shows great promise for developing industrial and biomedical applications‎.